2011
DOI: 10.4049/jimmunol.1003917
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Stellate Cells Function as Regulatory Bystanders

Abstract: Regulatory T cells (Treg) contribute significantly to the tolerogenic nature of the liver. The mechanisms however underlying liver-associated Treg induction are still elusive. We recently identified the vitamin A (VitA) metabolite, retinoic acid (RA), as a key-controller, which promotes TGF-β–dependent Foxp3+ Treg induction but inhibits TGF-β driven Th17 differentiation. To investigate whether the RA producing hepatic stellate cells (HSC) are part of the liver tolerance mechanism, we investigated the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 40 publications
5
130
0
1
Order By: Relevance
“…We provided quantified evidence of the existence of Type 1 and Type 2 LSEC, and the differences in intensity of markers expressed in PT and CV(see Supplementary Information), but quantification of cells such as sinusoidal endothelia must be interpretted with caution, our quantification provides further evidence of our observed findings, but it must be emphasized that the findings in this paper are intended to be descriptive. Stellate cells have been described as being aSMA mid32 , CD271 + 33 , and are CD146 + in animals 34 , lining the abluminal surface 32 of the sinus. We used aSMA and CD146 to clearly demarcate stellate cells from adjacent CD105 + LSEC and describe a lobular distribution of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…We provided quantified evidence of the existence of Type 1 and Type 2 LSEC, and the differences in intensity of markers expressed in PT and CV(see Supplementary Information), but quantification of cells such as sinusoidal endothelia must be interpretted with caution, our quantification provides further evidence of our observed findings, but it must be emphasized that the findings in this paper are intended to be descriptive. Stellate cells have been described as being aSMA mid32 , CD271 + 33 , and are CD146 + in animals 34 , lining the abluminal surface 32 of the sinus. We used aSMA and CD146 to clearly demarcate stellate cells from adjacent CD105 + LSEC and describe a lobular distribution of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…HSCs act as immune cells by expressing antigen presenting associated molecules, similar to LSECs and KCs, including MHC I, MHC II, CD80 and CD86 (17,18). In another study, HSCs failed to perform as APCs since expression of key molecules required for antigen presentation were not observed (19). HSCs may participate in immune regulation by other manners.…”
Section: The Liver As a Lymphoid Organmentioning
confidence: 99%
“…HSCs release inflammatory, proliferative, and fibrogenic cytokines such as IL-6, PDGF, and TGFb, through direct contact with their neighboring cells [18]. It is reported that HSCs can also function as regulatory bystander and contribute to liver-induced tolerance [19]. HSCs also contribute to liver regeneration [20], and potentially mediate sinusoidal blood flow via contraction and regulate microvascular structure and function in liver [21].…”
Section: Introductionmentioning
confidence: 99%